2018
DOI: 10.1101/403105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain connectivity dynamics: Multilayer network switching rate predicts brain performance

Abstract: Large-scale brain dynamics measures repeating spatiotemporal connectivity patterns that reflect a range of putative di↵erent brain states that underlie the dynamic repertoire of brain functions. The role of transition between brain networks is poorly understood and whether switching between these states is important for behavior has been little studied. Our aim here is to model switching between functional brain networks using multilayer network methods and test for associations between model parameters and be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…With a relatively long epoch length, patients are more likely to show lower flexibility, implying that the functional interaction ability may be impaired in patients with DOC. This observation is similar to the findings showing a positive correlation with the behavioral performance using fMRI data, which has a temporal resolution of at least 2 s in most cases [29,45,46]. In fact, previous studies have linked flexible reconfiguration of functional networks with learning, cognitive flexibility and working memory [30,47].…”
Section: Network Flexibility In Docsupporting
confidence: 90%
See 2 more Smart Citations
“…With a relatively long epoch length, patients are more likely to show lower flexibility, implying that the functional interaction ability may be impaired in patients with DOC. This observation is similar to the findings showing a positive correlation with the behavioral performance using fMRI data, which has a temporal resolution of at least 2 s in most cases [29,45,46]. In fact, previous studies have linked flexible reconfiguration of functional networks with learning, cognitive flexibility and working memory [30,47].…”
Section: Network Flexibility In Docsupporting
confidence: 90%
“…Functional brain networks were constructed using the EEG source connectivity method. The reconstructed regional time series were filtered in different frequency bands: delta (1-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Then the functional connectivity between the regional time series was computed using the phase locking value (PLV) for each frequency band [38].…”
Section: Brain Network Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the time series of dFC has long-range sequential correlations that vary across the human adult lifespan ( Battaglia et al, 2020 ) and specific temporal structures of several FC microstates have been reported to be subject-specific and heritable, and significantly linked to individual cognitive traits ( Vidaurre et al, 2017 ). Moreover, network switching in dFC is related to task performance and sleep ( Pedersen et al, 2018 ), attention ( Madhyastha et al, 2015 ), schizophrenia ( Damaraju et al, 2014 ), and depression ( Zheng et al, 2017 ). In particular, a growing body of researches links observed patterns of non-stationary switching between FC states with aspects of the underlying neural dynamics ( Hansen et al, 2015 ; Thompson, 2018 ), indicating short-term alteration in FC time series along with shifting in cognitive states.…”
Section: Introductionmentioning
confidence: 99%